Evaluation of the efficacy of a novel lumbar exoskeleton with multiple interventions for patients with lumbar disc herniation: a multicenter randomized controlled trial of non-inferiority - Huang, Xiaonan; Huang, Lele; Shi, Lei; Xu, Lifan; Cao, Chengbing; Wu, Heng; Cao, Min; Lv, Can; Shi, Ping; Zhang, Guohui; Fang, Fanfu (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundLumbar disc herniation (LDH) occurs when the nucleus pulposus or annulus fibrosus protrudes into the intervertebral space, potentially compressing nerve roots and causing symptoms such as sciatica, restricted mobility, and lower extremity weakness. The development of portable lumbar exoskeleton devices offers a new approach, combining traction, range of motion (ROM) exercises, and resistance training in a single system, potentially reducing treatment complexity and enhancing LDH patient outcomes.ObjectiveThis study aims to evaluate the efficacy and safety of a novel lumbar exoskeleton device compared to traditional traction methods combined with rehabilitation therapy for patients with LDH.MethodsA multicenter, non-inferiority randomized controlled trial was conducted with 118 participants diagnosed with LDH. Participants were randomly assigned to the Exoskeleton Group or the Traction Group. The Exoskeleton Group used the novel device for traction, ROM, and resistance training, while the Traction Group underwent traditional traction and rehabilitation therapy. Outcomes included efficacy rate after 10 treatments, Visual Analogue Scale (VAS), Oswestry Disability Index (ODI), and lumbar ROM—were assessed at 3, 6, and 10 treatments.ResultsA total of 118 eligible participants were recruited. After 10 treatments, both groups showed significant improvements in VAS scores, ODI, and lumbar ROM compared to baseline (P < 0.001). However, there was no significant difference in the overall efficacy rate between the two groups (P = 0.748).ConclusionThe novel lumbar exoskeleton device demonstrates comparable efficacy and safety to traditional traction therapy combined with rehabilitation, offering a promising alternative for the conservative treatment of LDH.